Direct Delivery of Apatite Nanoparticle-Encapsulated siRNA Targeting TIMP-1 for Intractable Abnormal Scars - Masayo Aoki; Noriko M. Matsumoto; Teruyuki Dohi; Hiroaki Kuwahawa; Satoshi Akaishi; Yuri Okubo; Rei Ogawa; Hirofumi Yamamoto; Kazuaki Takabe (Elsevier, 2020)
Hypertrophic scars (HSs) and keloids are histologically characterized by excessive extracellular matrix (ECM) deposition. ECM deposition depends on the balance between matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteases (TIMPs). TIMP-1 has been linked to ECM degradation and is therefore a promising therapeutic strategy. In this study, we generated super carbonate apatite (sCA) nanoparticle-encapsulated TIMP-1 small interfering RNA (siRNA) (siTIMP1) preparations and examined the effect of local injections on mouse HSs and on ex vivo-cultured keloids. The sCA-siTIMP1 injections significantly reduced scar formation, scar cross-sectional areas, collagen densities, and collagen types I and III levels in the lesions. None of the mice died or exhibited abnormal endpoints. Apatite accumulation was not detected in the other organs. In an ex vivo keloid tissue culture system, sCA-siTIMP1 injections reduced the thickness and complexity of collagen bundles. Our results showed that topical sCA-siTIMP1 injections during mechanical stress-induced HS development reduced scar size. When keloids were injected three times with sCA-siTIMP1 during 6 days, keloidal collagen levels decreased substantially. Accordingly, sCA-siRNA delivery may be an effective approach for keloid treatment, and further investigations are needed to enable its practical use.